Effect of anti‐CCR4 monoclonal antibody (mogamulizumab) on adult T‐cell leukemia–lymphoma: Cutaneous adverse reactions may predict the prognosis. Issue 3 (March 2014) - Yonekura, Kentaro; Kanzaki, Tamotsu; Gunshin, Kanayo; Kawakami, Nobuyo; Takatsuka, Yoshifusa; Nakano, Nobuaki; Tokunaga, Masahito; Kubota, Ayumu; Takeuchi, Shogo; Kanekura, Takuro; Utsunomiya, Atae
Abstract Adult T‐cell leukemia–lymphoma (ATL) is one of the most malignant lymphomas with poor prognosis. ATL cells express CC chemokine receptor 4 (CCR4) and mogamulizumab, a monoclonal antibody against CCR4 that exhibits very strong cytotoxicity for ATL cells via antibody‐dependent cellular cytotoxicity. Although its effect is dramatic in ATL, serious adverse reactions such as Stevens–Johnson syndrome have been reported. However, these eruptions can appear as therapeutic signs of mogamulizumab. We evaluated the effectiveness of mogamulizumab in five acute‐type ATL patients. Peripheral blood (PB) and lymph nodes (LN) were affected in three and four patients, respectively. In PB, complete response (CR) was obtained in all three patients and partial response (PR) was recorded in LN of one patient. In skin lesions, four of five patients manifested CR; in two, the lesions worsened after the start of mogamulizumab treatment and subsequently improved. In these lesions, CD4+8−25+ ATL cells were replaced by CD3+8+ cytotoxic T cells. Cutaneous adverse reactions (CAR) developed in two patients with CR; they did not show a relapse of ATL over the course of 9 months. Our findings suggest that mogamulizumab should be continued and surface marker evaluation should be performed even in patients whose skin lesions show aggravation, and that CAR may be a marker for a favorable prognosis.